2020
DOI: 10.1038/s41419-020-02973-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune signature driven by ADT-induced immune microenvironment remodeling in prostate cancer is correlated with recurrence-free survival and immune infiltration

Abstract: Androgen deprivation therapy (ADT) is a cornerstone treatment for locally advanced or metastatic prostate cancer (PCa). However, its potential effects on the tumor immune microenvironment (TIM) of PCa patients and the underlying mechanism remain largely unclear. To explore the effects of ADT on PCa TIM, RNA sequencing was performed on six paired pre-ADT biopsy and post-ADT PCa lesions, and five paired paracancerous benign tissues from patients receiving neoadjuvant ADT with locally advanced PCa. Bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 36 publications
0
53
0
1
Order By: Relevance
“…Studies in mouse models indicate direct immunomodulatory effects of ADT on the PCa TME; however, depending on the model used ( Pten −/− or MYC-driven, for example) distinct effects have been observed. A study of clinical samples of matched pre- and post-ADT early-stage PCa treated with neoadjuvant ADT indicated that treatment resulted in upregulation of immune checkpoints, such as PD-1 and CTLA-4, as well as infiltration of immune cells, including CD8 + and T h 1 cells ( Long et al 2020 ). However, this relatively small study (six matched biopsies) was unable to delineate the effects of distinct PCa subgroups in early stage disease.…”
Section: Androgen Deprivation Therapy and Immune Responses In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mouse models indicate direct immunomodulatory effects of ADT on the PCa TME; however, depending on the model used ( Pten −/− or MYC-driven, for example) distinct effects have been observed. A study of clinical samples of matched pre- and post-ADT early-stage PCa treated with neoadjuvant ADT indicated that treatment resulted in upregulation of immune checkpoints, such as PD-1 and CTLA-4, as well as infiltration of immune cells, including CD8 + and T h 1 cells ( Long et al 2020 ). However, this relatively small study (six matched biopsies) was unable to delineate the effects of distinct PCa subgroups in early stage disease.…”
Section: Androgen Deprivation Therapy and Immune Responses In Prostate Cancermentioning
confidence: 99%
“…Additionally, the typically high levels of sensitivity to ADT in this subgroup mean that careful consideration is needed to determine the optimal combination immunotherapy approach. ADT itself modulates the TME, as discussed above, with upregulation of genetic modules associated with antigen presentation, immune checkpoint genes and IFN-γ signalling ( Long et al 2020 ). Similar to radiotherapy and chemotherapy, ADT is imprecise in terms of modulating immune responses, resulting in upregulation of both pro- and anti-tumourigenic immune pathways, which may indeed be PCa subtype-dependent.…”
Section: Spop Loss In Prostate Cancermentioning
confidence: 99%
“…These findings showed that BOP1 affects DNA damage repair and hence plays a key role in carcinogenesis. Immune cell infiltration is closely related to clinical outcomes of cancer patients [ 30 , 31 ].We also evaluated how BOP1 expression correlated with the infiltration of 24 immune-related cells in 33 malignancies. We found that BOP1 was positively linked with the nTreg cell levels and negatively associated with the infiltrating Tcm cell, NK cell, and Tfh cell.…”
Section: Discussionmentioning
confidence: 99%
“…However a study from Kwon et al [6] , was in disagreement with the above findings and revealed no association between ADT treatment and its protection against COVID-19 infection. Subsequently, Klein et al [7] studying a cohort of prostate cancer patients who received ADT, the percentage rates of positive and negative COVID-19 cases were almost the same, 5.6% and 5.8% (OR = 0.93; P = 0.8), highlighting that ADT treatment does not appear to be protective against COVID-19 infection.…”
Section: Introductionmentioning
confidence: 98%